2019
DOI: 10.3390/plants8110497
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Composition and Antimicrobial Activity of Different Emirati Date (Phoenix dactylifera L.) Pits: A Comparative Study

Abstract: The biochemical composition, secondary metabolites (phenolic compounds, flavonoids) and antimicrobial potential of different varieties of Emirati date (Phoenix dactylifera L.) pits were investigated. Total phenolic acids (TPC) and total flavonoid contents (TFC) of the different date pits were measured using a Folin–Ciocalteau reagent. Different organic solvents [(n-hexane; H2O: EtOH (1:1); ethyl acetate; acetone: Water (1:1); and methanol: Chloroform (1:1)] were compared to evaluate the phytotoxicity of Ajwa, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 44 publications
3
19
0
1
Order By: Relevance
“…Some previous investigations showed that the total flavonoid contents were estimated for Algerian cultivars (15–299 mg QE/100 g dried weight), Iranian cultivars (1–81 mg CE/100 g dried weight), and Tunisian cultivars (6–54 mg QE/100 g fresh weight) [ 6 , 30 ]. These variations and differences could be because of various parameters such as age, location, applied agricultural practices, climatic conditions, storage, or even genetic factors [ 3 , 4 , 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some previous investigations showed that the total flavonoid contents were estimated for Algerian cultivars (15–299 mg QE/100 g dried weight), Iranian cultivars (1–81 mg CE/100 g dried weight), and Tunisian cultivars (6–54 mg QE/100 g fresh weight) [ 6 , 30 ]. These variations and differences could be because of various parameters such as age, location, applied agricultural practices, climatic conditions, storage, or even genetic factors [ 3 , 4 , 5 , 6 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the most famous types of edible fruit is date fruit. Date fruits are cheap and rich source of carbohydrates, proteins, amino acids, and essential minerals (zinc, copper, selenium, potassium, calcium, magnesium, phosphorus, manganese, and iron), fiber, vitamins (C and E), carotenoids, fatty acids, polyphenols and flavonoids [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The much great diversity of identified allelopathic compounds in nature implies a high variability in their mode of action. Works found in literature show that allelochemicals interfere with several and diverse metabolic processes in plants [ 38 , 39 , 40 ]. Application of cinnamic acid (100 μM) caused significant reduction in photosynthetic rate but there was no effect on efficiency and quantum yield of ΦPSII [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is supporting the idea that these mentioned extracts are affecting cell cycle, apoptosis and proliferation individually or all the three processes together. The use of crude extracts that are rich in phenolic and flavonoid contents ( Hussain et al, 2019 ) in addition to dietary constituents like fats, proteins, carbohydrates and dietary fibers might be the possible reason for the multi-effects of the extracts. Abu-Maan and Khalas varieties are sharing antibacterial and antifungal activities as well as anti-proliferative activities, where Khodari and Ajwa showed good antimicrobial potential, however inconsistent anti-proliferative activity.…”
Section: Discussionmentioning
confidence: 99%